The Comparative Analysis of Bribery in Armenia, Georgia and Azerbaijan: Gender, Age and Trust Issues. - Gulyk, Volodymyr (ADA University, 2013)
Aside such threats like terrorism, cyber-security, peace resolution or economic stability current academia often forgets about the inside factors of all the mentioned above issues. One of those according to me factors is institutionalized during the feudal ages phenomenon of corruption. Corruption is established in all the countries and does affect different sectors of public life. In Western democracies it is incorporated in the system and well monitored; in another is totally hidden and sometimes not controlled. In today's paper I am arguing that despite different types of the corruption and its characteristics it also has its social features, especially in developing countries. Today's paper is analyzing the objects of corruption in three post-soviet republics and describes this phenomenon accordingly to age, gender and trust issues. It does not say who is guilty or how to resolve the problem of corruption, but it does describes the contributors to the proliferation of the bribery on the ground.
Keywords: Public and International Affairs; Caucasus, South -- Economic conditions; Caucasus, South -- Bribe